ANALYSIS OF POWER GRIP AND PINCH GRIP AMONG HEALTH CARE PROFESSIONALS (International Journal of Physiotherapy, 2016)
Background: Grip and pinch strength are commonly employed indices of strength used in hand evaluations. Pinch grip and power grip strengths are used as indices of strength in hand therapy assessments. For all professions grip strength is an important criterion to be successful in their profession. Such phenomena may be explained by differences in nature of work, working environment, and objects workers handle.Method: 200 healthy subjects, satisfying the selection criteria were included and assessed with standardized procedure for power grip and pinch grip (lateral pinch, pad-pad, and tip-tip) strength. They were divided in four groups, 50 group each according to profession i.e. medical surgeons, dentist, physiotherapists and nurses.Results: The mean power grip strength shows highly significant difference between medical vs. dental (p>0.01) and medical vs. physiotherapy group (p> 0.05) .The mean lateral pinch strength shows there is highly significant difference (p< 0.001) between dental vs. nursing profession and dental vs. physiotherapy group. No significant difference among other groups. The mean pad-pad pinch strength shows there is significant difference between dental vs. nursing (p< 0.05) and dental vs physiotherapy group (p< 0.05). The mean Tip-Tip pinch strength shows there is significant difference between dental vs nursing profession(p< 0.05) and dental vs. physiotherapy(p< 0.05). No significant different among other groups.Conclusion: Surgeons have highest power grip strength followed by Nursing, Physiotherapy and Dental professionals. Dentists have the maximum pinch strength in all three positions, followed by Surgeons, Nurses and Physiotherapists. Surgeons have maximum pinch strength next to Dentists.